2015
DOI: 10.1155/2015/647930
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intravenous Ferric Carboxymaltose in Geriatric Inpatients at a German Tertiary University Teaching Hospital: A Retrospective Observational Cohort Study of Clinical Practice

Abstract: Current iron supplementation practice in geriatric patients is erratic and lacks evidence-based recommendations. Despite potential benefits in this population, intravenous iron supplementation is often withheld due to concerns regarding pharmacy expense, perceived safety issues, and doubts regarding efficacy in elderly patients. This retrospective, observational cohort study aimed to evaluate the safety and efficacy of intravenous ferric carboxymaltose (FCM, Ferinject) in patients aged >75 years with iron defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“… 60 Several recent studies have shown that intravenous iron application is also safe in geriatric patients with chronic inflammation-associated anemia. 66 68 Oral iron substitution is usually recommended in case of absolute iron deficiency. 69 Results of a recent meta-analysis of oral iron substitution in older patients indirectly confirms this recommendation by revealing an increase of Hb after 4–6 weeks of oral iron substitution.…”
Section: Management Options For Anemia In Frail Patientsmentioning
confidence: 99%
“… 60 Several recent studies have shown that intravenous iron application is also safe in geriatric patients with chronic inflammation-associated anemia. 66 68 Oral iron substitution is usually recommended in case of absolute iron deficiency. 69 Results of a recent meta-analysis of oral iron substitution in older patients indirectly confirms this recommendation by revealing an increase of Hb after 4–6 weeks of oral iron substitution.…”
Section: Management Options For Anemia In Frail Patientsmentioning
confidence: 99%
“…23 The absence of a significant response to oral iron supplementation can be attributed to a IDA misdiagnosis, malabsorption or persistent chronic blood loss that exceeds the amount of iron that can be absorbed from an oral supplement. 24,65,[72][73][74][75] The results of iron therapy for indications other than absolute IDA, such as cancer-related anemia, chronic kidney disease, chronic heart failure, inflammatory anemia and postoperative anemia, are not discussed here. 23,24,26,53,71 Several parenteral iron preparations are available, and the most commonly prescribed preparations are iron sucrose, ferric carboxymaltose and iron dextran.…”
mentioning
confidence: 99%
“…There is insufficient evidence that one iron preparation is superior over another, and the efficacy and safety of parenteral ferric carboxymaltose has been shown in heterogeneous groups of older patients. 24,65,[72][73][74][75] The results of iron therapy for indications other than absolute IDA, such as cancer-related anemia, chronic kidney disease, chronic heart failure, inflammatory anemia and postoperative anemia, are not discussed here. There are insufficient data to decide whether iron deficiency (low serum ferritin level with normal hemoglobin value) in older adults should be treated with iron.…”
mentioning
confidence: 99%
“…There was no difference between the geriatric and non-geriatric groups in terms of both ∆ hemoglobin and response rate. In a retrospective study investigating the efficacy of treatment in the hospitalized geriatric population over the age of 75, where oncology patients are underrepresented, the response rate was determined by similar criteria, and the response was observed in 18 of 38 patients (47.7%) [28]. The reason for reporting lower response rates in this study may be attributed to the inclusion of fewer patients, being in an older age group, or the fact that the patients were inpatients, a more vulnerable group.…”
Section: Discussionmentioning
confidence: 99%